Attendance of Students in Government Elementary Schools: A Study on Jharkhand - Ramakanta Mohalik; Rasmirekha Sethy; Ms. Sangeeta (Randwick International of Education and Linguistics Science Journal, 2021)
The main objective of this study is to explore the causes of low attendance of students in Government elementary schools. Survey method was adopted to conduct this study. Sample consists of 30 Head Teachers (HT) and 78 teachers selected through purposive sampling technique from Dhanbad and Lohardaga district of Jharkhand, India. Self-developed checklist with Yes or No options basing on different factors of low attendance was used as tool. The data were collected through Google form and analyzed by use of frequency count and percentage. It is found that causes such as working of both parents, involvement of children in domestic work, taking care of siblings, migration of parents for work, involvement in farming and harvesting, low aspiration of parents, abusive home environment, lack of interest of students in studies, poor in basic skills, lack of teachers and regular HTs in school, poor teaching strategy of teachers etc. are responsible for low attendance of students in elementary school. The study has suggested for coordinated effort from parents, School Management Committee (SMC), Government, teachers and HTs for increasing attendance of students. Further, it is suggested to provide non-formal education to illiterate parents so that they can realise the importance of education in one’s life.